Exosomes carring gag/env of ALV-J possess negative effect on immunocytes. (November 2017) - Wang, Guihua; Wang, Zhenzhen; Zhuang, Pingping; Zhao, Xiaomin; Cheng, Ziqiang
Abstract: J subgroup avian leukosis virus (ALV-J) is an exogenous retrovirus of avian. A key feature of ALV-J infection is leading to severe immunosuppressive characteristic of diseases. Viral components of retrovirus were reported closely associated with immunosuppression, and several similarities between exosomes and retrovirus preparations have lead to the hypotheses of retrovirus hijacker exosomes pathway. In this study, we purified exosomes from DF-1 cells infected and uninfected by ALV-J. Electron microscopy and mass spectrometry (MS) analysis showed that ALV-J not only increased the production of exosomes from ALV-J infected DF-1 cells (Exo-J) but also stimulated some proteins expression, especially ALV-J components secreted in exosomes. Immunosuppressive domain peptide (ISD) of envelope subunit transmembrane (TM) and gag of ALV-J were secreted in Exo-J. It has been reported that HIV gag was budded from endosome-like domains of the T cell plasma membrane. But env protein was first detected in exosomes from retrovirus infected cells. We found that Exo-J caused negative effects on splenocytes in a dose-dependant manner by flow cytometric analysis. And low dose of Exo-J activated immune activity of splenocytes, while high dose possessed immunosuppressive properties. Interestingly, Exo-J has no significant effects on the immunosuppression induced by ALV-J, and the immunosuppressive effects induced by Exo-J lower than that by ALV-J. Taken together, our data indicated that Exo-J supplied a microenvironment for the replication and transformation of ALV-J. Highlights: ALV-J infection increased the production of exosomes and changed the composition. The env and gag of ALV-J were secreted in Exo-J. Low dose of Exo-J activated immune activity of splenocytes, while high dose possessed negative properties. Exo-J has no effects on the immunosuppression induced by ALV-J. The negative effect induced by Exo-J was lower than ALV-J.